ESG Managerial Dilemmas in Microfinance Institutions: A Phenomenological Study of Practices and Values - Widya; Devi Yulia (Journal of Village Development Innovation, 2025)
The application of Environmental, Social, and Governance (ESG) principles in Microfinance Institutions (MFIs) is increasingly becoming a global concern, but presents its own challenges at the managerial level. MFI managers are often faced with ethical dilemmas between commitments to sustainability and operational pressures, especially in complex socio-economic contexts. This study aims to explore managers' subjective experiences in dealing with ESG managerial dilemmas and how local values influence decision-making. The method used is an interpretative phenomenology approach with in-depth interview techniques with 10 MFI managers in Indonesia. Data were analyzed through five stages of Interpretative Phenomenological Analysis (IPA), accompanied by observation and policy document analysis as triangulation. The results show four main forms of dilemma: (1) ESG compliance versus financial targets, (2) local social interests versus global ESG standards, (3) transparency versus operational confidentiality, and (4) ethical ambiguity in managerial decisions. Managers do not simply follow formal procedures, but navigate dilemmas through personal values, intuition, and community dialog. In conclusion, the implementation of ESG in MFIs demands a contextualized, reflective, and adaptive approach. This study emphasizes the importance of a flexible and local value-based ethical framework as part of the ESG strategy. This study also offers a theoretical contribution through strengthening the experiential dimension in microfinance ESG studies.